Additive grain-size: An innovative perspective to investigate the transformation among heavy metal and phosphorus fractions during aerobic composting. (15th August 2021) - Cui, Hu; Ou, Yang; Wang, Lixia; Yan, Baixing; Li, Yingxin; Bao, Meiwen
Abstract: Considerable researches have been devoted to ascertain the transformation among heavy metal (HM) or phosphorus (P) fractions during aerobic composting. However, available information that additives with different grain-sizes regulate the activation mechanism on P through influencing the passivation effect on HMs remains limited. Thus, this work aimed to investigate the dynamic changes in HM-fractions and P-fractions, and ascertain the interaction pathway between HMs and P during aerobic composting amended with medical stone (Coarse medical stone, 3–5 mm; Fine medical stone, < 0.1 mm). Medical stone, especially for coarse-grained medical stone, significantly enhanced the HM-passivation and P-activation during the composting ( P  < 0.05). The bioavailability factor of HMs decreased by 48.05% (Cu), 20.65% (Pb), 15.58% (Cd) and 6.10% (Zn), and the content of labile available P (LAP) increased by 6.45%. HMs, with the explanatory capacity of 65.9%–84.9%, was important parameter superior to temperature (0.8%–5.4%), moisture content (MC, 0.1%–1.7%), pH (0.1%–8.7%), electric conductivity (EC, 0.8%–9.8%), carbon-to-nitrogen (C:N, 0.3%–2.3%) ratio and dissolved organic carbon (DOC, 0.4%–3.1%), to evaluate the transformation among P-fractions. Our results cast a new light on P-activation with respect to HM-passivation during aerobic composting. Highlights: Coarse medical stone increased the temperature during the thermophilic phase. Coarse medical stone passivated heavy metals and activated phosphorus. HM-passivation mainly occurred during the maturation phase. NaHCO3 -Pi and HCl-Pi were main P-fractions. HMs was the primary factor controlling the transformation among P-fractions.